2018
DOI: 10.1016/j.heliyon.2018.e00967
|View full text |Cite
|
Sign up to set email alerts
|

WeChat use is significantly correlated with college students' quality of friendships but not with perceived well-being

Abstract: Although WeChat is currently one of the fastest growing social media in mainland China, many scholars and researchers are yet to systematically investigate the potential social and psychological consequences of the newly emerging online social network. Based on theory and previous studies, the principal purpose of this present study is to probe and understand whether and how the use of WeChat is related to individuals' friendship quality and psychological well-being. Research participants were a total of 508 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 62 publications
0
37
0
1
Order By: Relevance
“…We also compared the WUIQ score of the current PLS sample with 3 other available samples—2 college student samples and 1 elderly sample [ 27 , 48 , 49 ] in China. PLS had fewer WeChat friends than college students (mean 1.52 vs 2.34/2.44), and the percentage of PLS with more than 50 WeChat friends was similar to that of the elderly (50/163, 30.7% vs 12/35, 34.3%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also compared the WUIQ score of the current PLS sample with 3 other available samples—2 college student samples and 1 elderly sample [ 27 , 48 , 49 ] in China. PLS had fewer WeChat friends than college students (mean 1.52 vs 2.34/2.44), and the percentage of PLS with more than 50 WeChat friends was similar to that of the elderly (50/163, 30.7% vs 12/35, 34.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Continuous variables were described using mean and standard deviation, and categorical variables were described using frequency and percentage. WeChat use patterns in this study were compared with those of other populations in other studies using the same or similar scale [ 27 , 48 , 49 ]. WeChat users and nonusers were compared for sociodemographics by a two-tailed unpaired t test for age and χ 2 test for gender, marriage, education, and employment.…”
Section: Methodsmentioning
confidence: 99%
“…Such online self-presentation to a certain number of audiences makes people consciously or subconsciously try to make a favorable impression on others ( Grace et al., 2015 ). Existing researcher have suggested that social media provides an ideal setting for impression management in which users have more control over their impression management than in face-to-face communication ( Krämer and Winter, 2008 ; Pang, 2018 ). For example, users can decide which aspects of their lives and personalities they want to present and which photos convey the best images of them ( Ellison et al., 2006 ).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Overall, these results indicate that PLS had WeChat friend numbers similar to the elderly, spent time on WeChat similar to college students, and yet had higher emotional attachment to WeChat use than college students. [49] College students (N=508) [48] Undergraduates and graduates (N=339) [27] People living with schizophrenia (N=163) (this study) ). In addition, WeChat users had lower disability and higher general well-being scores than nonusers, but the differences only reached a trend level effect after matching.…”
Section: Wechat Use and Patternsmentioning
confidence: 99%